Hole recovery algorithm based on mobile inner nodes in wireless sensor networks - Kai YANG; Quan LIU; Shu-kui ZHANG; Jin LI; Dong-liang WENG (Tongxin xuebao)
To solve the problem of coverage holes in target areas,a principle for hole recovery was proposed.Based on the principle,a novel algorithm named SOI was proposed for hole recovery using mobile nodes,which does not require location information,figures out the optimal inner nodes in the edge of coverage holes,and then moves them to new po-sitions.Through this mechanism,the area of coverage holes could be reduced.Analysis and simulation results show that,SOI has a better performance in dense deployed wireless sensor networks compared with existing VHR algorithm.